-4r(r+6)=-57

Simple and best practice solution for -4r(r+6)=-57 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4r(r+6)=-57 equation:



-4r(r+6)=-57
We move all terms to the left:
-4r(r+6)-(-57)=0
We add all the numbers together, and all the variables
-4r(r+6)+57=0
We multiply parentheses
-4r^2-24r+57=0
a = -4; b = -24; c = +57;
Δ = b2-4ac
Δ = -242-4·(-4)·57
Δ = 1488
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$r_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$r_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1488}=\sqrt{16*93}=\sqrt{16}*\sqrt{93}=4\sqrt{93}$
$r_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-24)-4\sqrt{93}}{2*-4}=\frac{24-4\sqrt{93}}{-8} $
$r_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-24)+4\sqrt{93}}{2*-4}=\frac{24+4\sqrt{93}}{-8} $

See similar equations:

| (x-3)-(-4x+7)=5 | | 7/x=91 | | -4(5x-3)=112 | | 5m-3=18-2m | | 5x–14=6 | | 4x*2+25x=0 | | 18-4x=28+6x | | 3x−2= | | 3x−2=x | | k-1=k-5 | | -3(4x+1)-(2x+3)=0 | | 4c-40=-14c+14 | | 3(2x-4)=(12-x) | | 35g-29=14-8g | | 4(3x+6)=-24 | | 4x+43+2x-12=9x-26 | | 2x-15=7x-45 | | x-(3+2)=5 | | -30=5(x+1)−30 | | 2(x-10)-19(x-13)=-18x+3 | | 8=-2k-7+5k | | ƒ(x)=x2+8x+12. | | 3x-1+6x-11+8x-29=180 | | -3,7x/1,7=37 | | 10x+4=16x+18 | | 2n+6.2=-10.2 | | k–5=k–1 | | 11x+8=3x+9 | | k–5=k–1 | | 7n-4=317n | | 3m+16+2m+3m=180 | | -3y+4=5y+8 |

Equations solver categories